Pelaksanaan Peraturan Menteri Sosial - Nadiah Nadiah; Dermina Dalimunthe (Jurnal El-Thawalib, 2021)
Karang Taruna ia a community organization as a means of developing every member of the community that grows and develops on the basis of awareness and responsibility. However in Muaratais II Village Angkola Muaratais sub district, south Tapanuli Regency, the fuction of the youth Organization is still experiencing various promlems, one of wich is the potential of the younger generation and the community, the lack of attention from youth organization to providers of education and training for the community, and the lack community empowerment providers, especially the younger generation and the environment in a comprehensively integrated and directed manner and still experiencing many promlems due to thee lack of a sense of responsibility of society as individuals who have the potential and have a strong social sprit. From these problems, I want to know how the implementation of the Minister of Social Affairs Regulation Number 25 Year 2019 concerning the Function of Youth Organization in Muaratais District, Tapanuli Selatan Regency, what are the supporting and inhibiting factors, and how to riview Siyasah Fiqh on the implementation of the Minister of Social Affairs Regulation Number 25 of 2019 regarding the function youth organization in Muaratais II Village, Angkola Muaratais Sub-district, south Tapanuli Regency. The type of research used in this research I field research, using qualitative descriftive analysis methods, namely describing phenomena or events that data collection instruments used consisted of interviews, observations, and documentation. The result of this study are that the imolementation of the minister of social Affairs Regulation Number 25 of 2019 Article 6 paragraph (1) concerning yhe function of youth Organization in Muaratais